Pathogenic mitochondrial DNA 3243A>G mutation: From genetics to phenotype - Li, Danyang; Liang, Chunmei; Zhang, Tao; Marley, Jordan Lee; Zou, Weiwei; Lian, Muqing; Ji, Dongmei (Frontiers in Genetics, 2022)
The mitochondrial DNA (mtDNA) m.3243A>G mutation is one of the most common pathogenic mtDNA variants, showing very complex genetics, pathogenic molecular mechanisms, and phenotypes. In recent years, the prevention of mtDNA-related diseases has trended toward precision medicine strategies, such as preimplantation genetic diagnosis (PGD) and mitochondrial replacement therapy (MRT). These techniques are set to allow the birth of healthy children, but clinical implementation relies on thorough insights into mtDNA genetics. The genotype and phenotype of m.3243A>G vary greatly from mother to offspring, which compromises genetic counseling for the disease. This review is the first to systematically elaborate on the characteristics of the m.3243A>G mutation, from genetics to phenotype and the relationship between them, as well as the related influencing factors and potential strategies for preventing disease. These perceptions will provide clarity for clinicians providing genetic counseling to m.3243A>G patients.